Modified ultra-high molecular weight polyethylene, preparation method thereof and application of modified ultra-high molecular weight polyethylene in polyamide

By carrying out melt graft copolymerization reaction in a twin-screw extruder and introducing flow modifiers and crosslinking inhibitors, the problem of difficult continuous extrusion processing of maleic anhydride grafted ultra-high molecular weight polyethylene is solved, simplified and continuous production of the process is achieved, and the performance of polyamide materials is improved.

CN119798546APending Publication Date: 2025-04-11NANJING JULONG SCIENCE & TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411984336.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, maleic anhydride grafted ultra-high molecular weight polyethylene is difficult to perform continuous extrusion processing, and the preparation process of modified nylon 66 is cumbersome, making continuous production difficult.

Method used

The melt graft copolymerization reaction is carried out using a twin-screw extruder. By introducing a flow modifier of hollow glass microbeads and nanomontmorillonite, the melt flowability of ultra-high molecular weight polyethylene is improved, and a crosslinking inhibitor is added to the process to control the crosslinking side reaction.

Benefits of technology

The continuous extrusion processing of maleic anhydride grafted ultra-high molecular weight polyethylene is realized, which simplifies the process flow and is suitable for continuous production, while maintaining the excellent mechanical properties and wear resistance of polyamide materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222213310000101
    Figure BDA0005222213310000101
  • Figure BDA0005222213310000111
    Figure BDA0005222213310000111
Patent Text Reader

Abstract

The invention discloses modified ultra-high molecular weight polyethylene, a preparation method of the modified ultra-high molecular weight polyethylene and application of the modified ultra-high molecular weight polyethylene in polyamide. The modified ultra-high molecular weight polyethylene comprises the following components in parts by weight: 20-40 parts of ultra-high molecular weight polyethylene A; 53-61 parts by weight of ultra-high molecular weight polyethylene B; 6-12 parts by weight of a flow modifier; 0.5 to 1.0 part by weight of a lubricant A; 0.9-3 parts by weight of maleic anhydride; 0.09 to 0.3 part by weight of an initiator; 0.1 to 0.2 part by weight of a crosslinking inhibitor; the viscosity average molecular weight of the ultra-high molecular weight polyethylene A is 150000-250000; the viscosity average molecular weight of the ultra-high molecular weight polyethylene B is greater than or equal to 4 million. The modified ultra-high molecular weight polyethylene prepared by the invention can realize continuous extrusion processing production, and the applied polyamide material has the characteristics of low friction coefficient, low abrasion and mutual balance of rigidity and toughness, and can be used for easily-worn railway locomotive accessories, such as a center plate abrasion plate, a side bearing abrasion plate and the like, as well as easily-worn automobile accessories, so that the service life of the automobile accessory is prolonged. And therefore, the device has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a modified ultra-high molecular weight polyethylene, a preparation method thereof and an application thereof in polyamide. Background Art

[0002] Ultra-high molecular weight polyethylene is an engineering plastic with a linear structure. It has good impact resistance, wear resistance, corrosion resistance, self-lubrication, low temperature resistance and other characteristics. However, due to the high molecular weight and long molecular chain of ultra-high molecular weight polyethylene, it is easy to entangle with each other and has poor fluidity. During the melt extrusion or injection molding process, it is easy to block the compression section of the screw and rotate with the screw, and it cannot be transported forward. Therefore, it is difficult to extrude or injection mold it alone. Polyamide (commonly known as nylon) has high mechanical strength and self-lubrication, but in special cases, polyamide cannot meet the wear resistance requirements of parts and components, and it is necessary to add additional wear-resistant agents to improve the wear resistance of composite materials. The use of ultra-high molecular weight polyethylene to modify polyamide to prepare polyamide alloy materials can effectively improve the wear resistance of polyamide alloy materials. In this regard, a Chinese patent with patent number CN201310405628.5 discloses an ultra-high molecular weight polyethylene modified nylon 66 and a preparation method thereof, which is an alloy material composed of ultra-high molecular weight polyethylene grafted with heterogeneous maleic anhydride and nylon 66. The heterogeneous chemical grafting method mentioned in the patent (according to "Modern Plastic Processing Applications" No. 3, 1993, pages 26-30) is to hot-press the ultra-high molecular weight polyethylene resin into a 0.1-0.3 mm thin sheet, and then put it into an acetic anhydride solution containing 30% maleic anhydride, electromagnetically stir, and react at 80-120°C to finally obtain an ultra-high molecular weight polyethylene with a heterogeneous surface grafted maleic anhydride with an overall maleic anhydride grafting rate of 0.5-0.8%. When preparing ultra-high molecular weight polyethylene modified nylon 66, nylon 66 and heterogeneous maleic anhydride grafted ultra-high molecular weight polyethylene are first dried at 105°C for 4 hours, and then all the materials are added to a high-speed mixer according to the above proportions and mixed evenly, and then transferred to a parallel co-rotating twin-screw extruder of φ36-65mm, L / D=36-42 for extrusion granulation to prepare ultra-high molecular weight polyethylene modified nylon 66. It can be seen that although this process can realize the mixed extrusion processing of ultra-high molecular weight polyethylene and nylon 66, the ultra-high molecular weight polyethylene modification process and the entire preparation process of modified nylon 66 are relatively cumbersome, and are only suitable for intermittent small-batch experimental research, and it is difficult to achieve continuous production. Summary of the invention

[0003] The present invention aims to solve the technical problem that maleic anhydride grafted ultra-high molecular weight polyethylene is difficult to be continuously extruded in the prior art; a modified ultra-high molecular weight polyethylene, a preparation method thereof and application in polyamide are proposed to achieve continuous extrusion of maleic anhydride grafted ultra-high molecular weight polyethylene, while the applied polyamide material can maintain excellent mechanical properties and wear resistance.

[0004] In order to achieve the above object, the present invention adopts the following technical scheme:

[0005] A modified ultra-high molecular weight polyethylene comprises the following components in parts by weight:

[0006] Ultra high molecular weight polyethylene A 20-40 parts by weight;

[0007] Ultra high molecular weight polyethylene B 53-61 parts by weight;

[0008] 6-12 parts by weight of flow modifier;

[0009] Lubricant A 0.5-1.0 parts by weight;

[0010] Maleic anhydride 0.9-3 parts by weight;

[0011] Initiator 0.09-0.3 parts by weight;

[0012] 0.1-0.2 parts by weight of a cross-linking inhibitor;

[0013] The viscosity average molecular weight of the ultra-high molecular weight polyethylene A is 1.5-2.5 million; the viscosity average molecular weight of the ultra-high molecular weight polyethylene B is ≥4 million.

[0014] Furthermore, the maleic anhydride grafting rate of the modified ultra-high molecular weight polyethylene is 0.7-1.5%.

[0015] Furthermore, the melt mass flow rate of the modified ultra-high molecular weight polyethylene is 1.0-5.0 g / 10 min, wherein the flow rate test load is 2.16 kg and the test temperature is 190°C.

[0016] Furthermore, the flow modifier is a mixture of hollow glass microspheres and nano-montmorillonite; the addition ratio of the hollow glass microspheres to the nano-montmorillonite in the mixture is 2:1.

[0017] Furthermore, the density of the hollow glass microspheres is 0.95-1.50 g / cm 3 , D90 particle size is 10-30μm, and compressive strength is ≥80MPa.

[0018] Furthermore, the lubricant A is silicone powder.

[0019] Furthermore, the initiator is one of diisopropylbenzene peroxide (DCP), benzoyl peroxide (BPO), and di-tert-butyl diisopropylbenzene peroxide (BIPB).

[0020] Furthermore, the cross-linking inhibitor is zinc dimethyldithiocarbamate.

[0021] Furthermore, the preparation method of the modified ultra-high molecular weight polyethylene comprises the following steps:

[0022] S1. Mix ultra-high molecular weight polyethylene A, ultra-high molecular weight polyethylene B, flow modifier, lubricant A, maleic anhydride, initiator and cross-linking inhibitor in a high-speed mixer according to weight proportions to obtain a mixture. The mixing time is 3-5 minutes, and heating is not required during the mixing process;

[0023] S2, the mixture is placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, extrusion granulation, cooling, dehydration, and blast drying to obtain the modified ultra-high molecular weight polyethylene. Wherein, the processing temperature control range of each zone of the parallel co-rotating twin-screw extruder is 170-200°C, the head temperature control range of the parallel co-rotating twin-screw extruder is 190±5°C, and the vacuum degree of the parallel co-rotating twin-screw extruder is ≤-0.08MPa.

[0024] A polyamide material comprises the following components in parts by weight:

[0025] Modified ultra-high molecular weight polyethylene: 10-15 parts by weight,

[0026] Polyamide resin: 73-89 parts by weight,

[0027] Poly(m-xylylene adipamide) resin: 4-8 parts by weight,

[0028] Lubricant B: 0.2-0.5 parts by weight,

[0029] Auxiliary agent: 1-3 parts by weight;

[0030] Wherein, the modified ultra-high molecular weight polyethylene is any one of the modified ultra-high molecular weight polyethylenes mentioned above.

[0031] Furthermore, the polyamide resin is at least one of PA6, PA66, PA56, PA610, PA612, PA11, PA12, PA1010, and PA1012; and the relative viscosity of the polyamide resin is ≥2.0dl / g.

[0032] Furthermore, the relative viscosity of the poly(meta-xylylene adipamide) resin (PA MXD6) is ≥2.0 dl / g.

[0033] Furthermore, the lubricant B is one of modified ethylene bis fatty acid amide (TAF for short), silicone masterbatch, montan wax, or a mixture of any two or more thereof in any ratio.

[0034] Furthermore, the silicone masterbatch contains more than 50% ultra-high molecular weight siloxane, and the remaining carrier resin is LDPE or PA6; the montan wax is a mixture of OP wax and E wax; and the addition ratio of OP wax to E wax in the mixture of OP wax and E wax is 2:1.

[0035] Furthermore, the auxiliary agent is at least one of an antioxidant, a photoaging auxiliary agent, and a colorant.

[0036] The antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the ratio of the added amount of antioxidant 1098 to antioxidant 168 in the mixture of the hindered phenol antioxidant and the phosphite antioxidant is 1:1;

[0037] The light aging agent is a mixture of an ultraviolet absorber and a light stabilizer; the ultraviolet absorber is UV-234; the light stabilizer is UV-944; the addition ratio of UV-234 to UV-944 in the mixture of the ultraviolet absorber and the light stabilizer is 1:1.

[0038] A method for preparing the polyamide material as described above comprises the following steps:

[0039] The modified ultra-high molecular weight polyethylene, polyamide resin, poly(m-xylylene adipamide) resin, lubricant B and auxiliary agents are uniformly mixed according to weight proportions, melt-blended, extruded and granulated through a parallel co-rotating twin-screw extruder to obtain the polyamide material.

[0040] The beneficial effects of the present invention are:

[0041] The present invention uses ultra-high molecular weight polyethylene as a graft copolymerization matrix resin, polar reaction group maleic anhydride as a graft copolymerization monomer, and uses a twin-screw extruder as a container for melt graft copolymerization to prepare maleic anhydride grafted modified ultra-high molecular weight polyethylene under molten conditions. Compared with other process routes, the melt graft copolymerization carried out in the twin-screw extruder has the characteristics of high production efficiency, simple preparation process, and continuous production. The flow modifier of hollow glass microspheres and nano-montmorillonite composite is introduced into the formula system, which has a good synergistic effect, improves the melt fluidity of the ultra-high molecular weight polyethylene, and enables the ultra-high molecular weight polyethylene to be extruded in a twin-screw extruder. Among them, the hollow glass microspheres can be well adsorbed on the surface of the ultra-high molecular weight polyethylene, because of its spherical structure, smooth and round shape, isotropic, and has no sharp corners, so that the hollow glass microspheres can play a "rolling ball" effect in the ultra-high molecular weight polyethylene matrix. After the ultra-high molecular weight polyethylene matrix adsorbs hollow glass microspheres, it has fluidity and can be smoothly intercalated between the nano-montmorillonite sheets to form a unique spatial network structure. Nano-montmorillonite belongs to layered silicates. The montmorillonite sheets have great rigidity and respond quickly when subjected to force. The montmorillonite sheets can drive the ultra-high molecular weight polyethylene macromolecules to move, disentangle the ultra-high molecular weight polyethylene macromolecules, and further improve the flow properties of the material. At the same time, zinc dimethyl dithiocarbamate is introduced as a cross-linking inhibitor. Under the action of the initiator, zinc dimethyl dithiocarbamate can generate new free radicals-dithiocarbamoyl free radicals. An appropriate amount of dithiocarbamoyl free radicals can effectively reduce the cross-linking side reactions of the ultra-high molecular weight polyethylene macromolecule chain and reduce the cross-linking byproducts of the ultra-high molecular weight polyethylene macromolecule chain. In addition, the formula system is matched with low molecular weight ultra-high molecular weight polyethylene A and high molecular weight ultra-high molecular weight polyethylene B, which can take into account both fluidity and wear resistance. The molecular chain of low molecular weight ultra-high molecular weight polyethylene A is easily disentangled by the flow modifier, and the fluidity is better. High molecular weight ultra-high molecular weight polyethylene B can maintain the regularity of the molecular chain and has better wear resistance.

[0042] The polyamide material prepared by the present invention not only solves the problem of poor compatibility between ultra-high molecular weight polyethylene and polyamide, but also maintains the wear resistance of ultra-high molecular weight polyethylene itself by grafting maleic anhydride, a polar reaction group, on the ultra-high molecular weight polyethylene molecular chain. In order to further improve the mechanical strength and wear resistance of the polyamide material, poly(m-phenylenediamine adipamide) resin is introduced. Poly(m-phenylenediamine adipamide) resin is a semi-aromatic polyamide resin, which is polycondensed from adipic acid and m-phenylenediamine, and has the characteristics of excellent mechanical properties, wear resistance and thermal properties. Poly(m-phenylenediamine adipamide) resin can be miscible with polyamide resin in any proportion, and can have good compatibility with ultra-high molecular weight polyethylene grafted with maleic anhydride. However, since its molecular chain contains benzene rings and has high crystallinity, the material is hard and brittle, so it should be added in an appropriate amount.

[0043] The polyamide material prepared by the present invention can be used for easily worn railway locomotive accessories, such as center plate wear plates, side bearing wear plates, etc., and easily worn automobile accessories, such as gears, guide rails, etc., and has broad application prospects. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present application will be clearly and completely described below in combination with the technical scheme of the embodiment. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In the description of the present application, the experimental methods, unless otherwise specified, are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.

[0045] The disclosure below provides many different embodiments or examples to implement the present application. In order to simplify the disclosure of the present application, the components and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. Those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.

[0046] The sources of the main raw materials in the following embodiments and comparative examples of the present invention are as follows:

[0047] Ultra-high molecular weight polyethylene A grade is MIPELON XM-220, density 0.94g / cm 3 , viscosity average molecular weight 2 million, purchased from Mitsui Chemicals, Inc.;

[0048] Ultra-high molecular weight polyethylene B grade is LL-4060, density 0.94g / cm 3 , viscosity average molecular weight 4.5 million, purchased from Shanghai Lianle Chemical Technology Co., Ltd.;

[0049] Hollow glass microspheres are graded HM15, with a true density of 1.25 g / cm 3 , compressive strength 124.11MPa, particle size D90 15μm, purchased from Zhengzhou Shenglait Hollow Microsphere New Material Co., Ltd.;

[0050] The grade of nano-montmorillonite is DK4, with a density of 1.7g / cm 3 , fineness 200 mesh, purchased from Zhejiang Fenghong New Materials Co., Ltd.;

[0051] The silicone powder was KJ-B01 with an average particle size of 200 nm and a viscosity-average molecular weight of 500,000, purchased from Hangzhou Kaijie Plastic Technology Co., Ltd.

[0052] Maleic anhydride, CAS registration number: 108-31-6, purchased from Zibo Qixiang Tengda Chemical Co., Ltd.;

[0053] Di-tert-butyl peroxide diisopropylbenzene (BIPB) brand: FARIDA BIPB96, CAS registration number: 25155-25-3, purchased from Hunan Fangruida Technology Co., Ltd.;

[0054] Zinc dimethyldithiocarbamate, active substance content 97%, CAS registration number: 137-30-4, purchased from Hebi Lianhao Chemical Co., Ltd.;

[0055] The polyamide 6 (PA6) resin was HY-2800 with a relative viscosity of 2.8 dl / g and was purchased from Haiyang Technology Co., Ltd.;

[0056] The polyamide 66 (PA66) resin was EPR24 with a relative viscosity of 2.4 dl / g and was purchased from Shenma Industrial Co., Ltd.

[0057] Poly(m-phenylenediamine adipamide) (PA MXD6) resin grade is M30, density is 1.18g / cm 3 , purchased from Beijing Anage Energy Engineering Technology Co., Ltd.;

[0058] The silicone masterbatch was GT-500, the carrier resin was LLDPE, and the content of ultra-high molecular weight siloxane was 60%, purchased from Zhejiang Jiahua Fine Chemical Co., Ltd.

[0059] The OP wax brand is Licowax OP, purchased from Clariant;

[0060] The brand of E wax is Licowax E, purchased from Clariant;

[0061] The brand of antioxidant 1098 is Irganox 1098, CAS registration number: 23128-74-7, purchased from BASF;

[0062] The brand of antioxidant 168 is Irganox 168, CAS registration number: 31570-04-4, purchased from BASF;

[0063] The brand of ultraviolet absorber UV-234 is Tinuvn 234, CAS registration number: 70321-86-7, purchased from BASF;

[0064] The light stabilizer is UV-944, the brand is Chimassorb 944, CAS registration number: 71878-19-8, purchased from BASF;

[0065] The remaining reagents were commercially available products.

[0066] The detection methods used in the performance detection of the corresponding products in the embodiments and comparative examples of the present invention are as follows:

[0067] First, the polyamide material is placed in an injection molding machine to make a standard sample, and then the performance test is carried out. Among them, the injection molding temperature of polyamide 6 (PA6) is 250-275℃, and the injection molding temperature of polyamide 66 (PA66) is 270-300℃.

[0068] The tensile strength was determined according to ISO 527 method, with a gauge length of 75 mm and a test speed of 5 mm / min;

[0069] The flexural strength was determined according to ISO 178 method, with a span of 64 mm and a test speed of 2 mm / min;

[0070] The notched impact strength of the simply supported beam was determined according to ISO 179 method, with a pendulum energy of 4J;

[0071] The friction and wear performance was tested according to GB / T 3960-2016. The sample size was 30mm×7mm×6mm. The grinding ring was made of 45# steel. The outer diameter of the steel ring was 40mm and the inner diameter was 16mm. The test ring speed was 200r / min, the test time was 2h, and the load was 196N. All tests were carried out under non-lubricated conditions (dry friction).

[0072] Example 1

[0073] A method for preparing a polyamide material comprises the following steps: uniformly mixing 15 kg of modified ultra-high molecular weight polyethylene, 75 kg of PA6 resin, 7 kg of poly(m-xylylene adipamide) resin, 0.3 kg of lubricant and 2.7 kg of additive, melt blending, extruding and granulating through a parallel co-rotating twin-screw extruder to obtain the polyamide material, which is recorded as S1.

[0074] Wherein, the preparation method of the modified ultra-high molecular weight polyethylene is:

[0075] S1, 2.8kg ultra-high molecular weight polyethylene A, 6.043kg ultra-high molecular weight polyethylene B, 0.6kg hollow glass microspheres, 0.3kg nano-montmorillonite, 0.05kg silicone powder, 0.17kg maleic anhydride, 0.017kg dicumyl peroxide and 0.02kg zinc dimethyldithiocarbamate are placed in a high-speed mixer and mixed uniformly according to weight to obtain a mixture. The mixing time is 3-5 minutes, and the mixing process does not require heating;

[0076] S2, the mixture is placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, extrusion granulation, cooling, dehydration, and blast drying to obtain the modified ultra-high molecular weight polyethylene. Wherein, the processing temperature control range of each zone of the parallel co-rotating twin-screw extruder is 170-200°C, the head temperature control range of the parallel co-rotating twin-screw extruder is 190±5°C, and the vacuum degree of the parallel co-rotating twin-screw extruder is ≤-0.08MPa.

[0077] The maleic anhydride grafting rate of the obtained modified ultra-high molecular weight polyethylene is 1.1%; the grafting rate of maleic anhydride can be measured by a conventional grafting rate test method in the art, such as acid-base titration (chemical titration method) test; the melt mass flow rate of the modified ultra-high molecular weight polyethylene is 2.5g / 10min, wherein the flow rate test load is 2.16kg, and the flow rate test temperature is 190°C.

[0078] The lubricant is silicone masterbatch; the auxiliary agent is an antioxidant, and the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; and the added ratio of antioxidant 1098 to antioxidant 168 in the mixture of the hindered phenol antioxidant and the phosphite antioxidant is 1:1.

[0079] Example 2

[0080] A method for preparing a polyamide material comprises the following steps: uniformly mixing 12 kg of modified ultra-high molecular weight polyethylene, 81 kg of PA6 resin, 5 kg of poly(m-xylylene adipamide) resin, 0.5 kg of lubricant and 1.5 kg of additive, melt blending, extruding and granulating through a parallel co-rotating twin-screw extruder to obtain the polyamide material, which is recorded as S2.

[0081] The modified ultra-high molecular weight polyethylene, lubricant and additives used in this embodiment are the same as those in Example 1.

[0082] Example 3

[0083] A method for preparing a polyamide material comprises the following steps: uniformly mixing 10 kg of modified ultra-high molecular weight polyethylene, 81.5 kg of PA66 resin, 6 kg of poly(m-xylylene adipamide) resin, 0.5 kg of lubricant and 2 kg of additive, melt blending, extruding and granulating through a parallel co-rotating twin-screw extruder to obtain the polyamide material, which is recorded as S3.

[0084] The modified ultra-high molecular weight polyethylene used in this embodiment is consistent with that in embodiment 1.

[0085] The lubricant is a mixture of OP wax and E wax in a mass ratio of 2:1;

[0086] The auxiliary agent is a photoaging agent, which is a mixture of an ultraviolet light absorber and a light stabilizer; the ultraviolet light absorber is UV-234; the light stabilizer is UV-944; the mass ratio of UV-234 to UV-944 in the mixture of the ultraviolet light absorber and the light stabilizer is 1:1.

[0087] Example 4

[0088] The difference between this embodiment and the above-mentioned embodiment 1 is that the modified ultra-high molecular weight polyethylene used in preparing a polyamide material is different, and the remaining method steps are consistent with those of embodiment 1. Among them, the preparation method of the modified ultra-high molecular weight polyethylene used in this embodiment is as follows:

[0089] S1, 3.8kg ultra-high molecular weight polyethylene A, 5.214kg ultra-high molecular weight polyethylene B, 0.4kg hollow glass microspheres, 0.2kg nano-montmorillonite, 0.09kg silicone powder, 0.26kg maleic anhydride, 0.026kg benzoyl peroxide and 0.01kg zinc dimethyl dithiocarbamate are placed in a high-speed mixer and mixed uniformly according to weight to obtain a mixture. The mixing time is 3-5 minutes, and the mixing process does not require heating;

[0090] S2, the mixture is placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, extrusion granulation, cooling, dehydration, and blast drying to obtain the modified ultra-high molecular weight polyethylene. Wherein, the processing temperature control range of each zone of the parallel co-rotating twin-screw extruder is 170-200°C, the head temperature control range of the parallel co-rotating twin-screw extruder is 190±5°C, and the vacuum degree of the parallel co-rotating twin-screw extruder is ≤-0.08MPa.

[0091] The maleic anhydride grafting rate of the modified ultra-high molecular weight polyethylene obtained by the above preparation method is 1.3%; the grafting rate of maleic anhydride can be measured by a conventional grafting rate test method in the art, such as acid-base titration (chemical titration method) test; the melt mass flow rate of the modified ultra-high molecular weight polyethylene is 3.0g / 10min, wherein the flow rate test load is 2.16kg, and the flow rate test temperature is 190°C.

[0092] The polyamide material obtained in this example is recorded as S4.

[0093] Comparative Example 1

[0094] In this comparative example 1, hollow glass microspheres and nano-montmorillonite were not added when preparing the modified ultra-high molecular weight polyethylene, and the remaining components and preparation steps were consistent with those of Example 1. During the preparation of the modified ultra-high molecular weight polyethylene, after the materials were mixed, they were placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, and continuous extrusion could not be performed, that is, the modified ultra-high molecular weight polyethylene could not be obtained in the end. This comparative example 1 is recorded as D1.

[0095] Comparative Example 2

[0096] The difference between this comparative example 2 and the above-mentioned embodiment 1 is that the modified ultra-high molecular weight polyethylene used is different, and the other method steps are consistent with embodiment 1. Among them, the modified ultra-high molecular weight polyethylene used in this comparative example 2 is not added with nano-montmorillonite during preparation, but is modified with hollow glass microspheres alone, and its specific preparation method is as follows:

[0097] S1. 2.8 kg ultra-high molecular weight polyethylene A, 6.043 kg ultra-high molecular weight polyethylene B, 0.9 kg hollow glass microspheres, 0.05 kg silicone powder, 0.17 kg maleic anhydride, 0.017 kg dicumyl peroxide and 0.02 kg zinc dimethyldithiocarbamate are placed in a high-speed mixer and mixed uniformly according to weight to obtain a mixture. The mixing time is 3-5 minutes, and the mixing process does not require heating;

[0098] S2, the mixture is placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, extrusion granulation, cooling, dehydration, and blast drying to obtain the modified ultra-high molecular weight polyethylene. Wherein, the processing temperature control range of each zone of the parallel co-rotating twin-screw extruder is 170-200°C, the head temperature control range of the parallel co-rotating twin-screw extruder is 190±5°C, and the vacuum degree of the parallel co-rotating twin-screw extruder is ≤-0.08MPa.

[0099] The maleic anhydride grafting rate of the modified ultra-high molecular weight polyethylene obtained by the above preparation method is 0.7%; the grafting rate of maleic anhydride can be measured by a conventional grafting rate test method in the art, such as acid-base titration (chemical titration method) test; the melt mass flow rate of the modified ultra-high molecular weight polyethylene is 0.9g / 10min, wherein the flow rate test load is 2.16kg, and the flow rate test temperature is 190°C.

[0100] The polyamide material obtained in this comparative example is recorded as D2.

[0101] Comparative Example 3

[0102] The difference between this comparative example 3 and the above-mentioned embodiment 1 is that the modified ultra-high molecular weight polyethylene used is different, and the other method steps are consistent with embodiment 1. Among them, the modified ultra-high molecular weight polyethylene used in this comparative example 3 is not added with the cross-linking inhibitor zinc dimethyl dithiocarbamate during preparation, and its specific preparation method is as follows:

[0103] S1, 2.8kg ultra-high molecular weight polyethylene A, 6.063kg ultra-high molecular weight polyethylene B, 0.6kg hollow glass microspheres, 0.3kg nano-montmorillonite, 0.05kg silicone powder, 0.17kg maleic anhydride, 0.017kg diisopropylbenzene peroxide are placed in a high-speed mixer and mixed uniformly according to weight to obtain a mixture. The mixing time is 3-5 minutes, and the mixing process does not require heating;

[0104] S2, the mixture is placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, extrusion granulation, cooling, dehydration, and blast drying to obtain the modified ultra-high molecular weight polyethylene. Wherein, the processing temperature control range of each zone of the parallel co-rotating twin-screw extruder is 170-200°C, the head temperature control range of the parallel co-rotating twin-screw extruder is 190±5°C, and the vacuum degree of the parallel co-rotating twin-screw extruder is ≤-0.08MPa.

[0105] The maleic anhydride grafting rate of the obtained modified ultra-high molecular weight polyethylene is 0.8%; the grafting rate of maleic anhydride can be measured by a conventional grafting rate test method in the art, such as acid-base titration (chemical titration method) test; the melt mass flow rate of the modified ultra-high molecular weight polyethylene is 1.2g / 10min, wherein the flow rate test load is 2.16kg, and the flow rate test temperature is 190°C.

[0106] The polyamide material obtained in this comparative example is recorded as D3.

[0107] Comparative Example 4

[0108] A method for preparing a polyamide material comprises the following steps: uniformly mixing 15 kg of modified ultra-high molecular weight polyethylene, 82 kg of PA6 resin, 0.3 kg of lubricant and 2.7 kg of auxiliary agent, melt blending, extruding and granulating through a parallel co-rotating twin-screw extruder to obtain the polyamide material, which is recorded as D4.

[0109] The modified ultra-high molecular weight polyethylene, lubricant and additives used in this comparative example 4 are consistent with those in Example 1. The difference between this comparative example 4 and the above-mentioned Example 1 is that the poly(meta-xylylene adipamide) resin is replaced with PA6 resin of the same mass, that is, the poly(meta-xylylene adipamide) resin is not added to the components.

[0110] Performance testing

[0111] In order to better verify the mechanical properties and wear resistance of the polyamide materials obtained in the above embodiments and comparative examples, the composite materials obtained in the above embodiments 1-4 and comparative examples 1-4 are tested for various properties such as tensile strength, flexural strength, notched impact strength and wear resistance (friction coefficient, wear loss), and the test results are as follows:

[0112]

[0113]

[0114] It can be seen from the preparation process and test data of Examples 1 to 4 of the present application that the modified ultra-high molecular weight polyethylene prepared by the method of the present invention can be prepared by continuous extrusion, and the use of the modified ultra-high molecular weight polyethylene to fill the polyamide material can make the polyamide material have both excellent mechanical properties and wear resistance. Among them, the tensile strength of the filled polyamide 6 (PA6) material (Example 1, Example 2 and Example 4) is above 65MPa, the flexural strength is above 75MPa, and the notched impact strength is 8.8KJ / m 2The friction coefficient is below 0.138, and the mass wear is 0.0001g. The tensile strength of the filled polyamide 66 (PA66) material (Example 3) is 80MPa, the bending strength is 88MPa, and the notched impact strength is 7.1KJ / m 2 , the friction system is 0.126, and the mass wear is 0.0001g.

[0115] It can be seen from the test results of Comparative Example 1 that when hollow glass microspheres and nano-montmorillonite are not added to the components, the fluidity of ultra-high molecular weight polyethylene is very poor and continuous extrusion cannot be completed. This shows that the use of hollow glass microspheres and nano-montmorillonite to modify ultra-high molecular weight polyethylene is the key to enabling continuous extrusion of ultra-high molecular weight polyethylene.

[0116] It can be seen from the test data of Example 1 and Comparative Example 2 that the mechanical properties and wear resistance of Comparative Example 2 are significantly lower than those of Example 1. The possible reason is that no nano-montmorillonite is added to the modified ultra-high molecular weight polyethylene during preparation. Simply relying on hollow glass microbeads can only improve fluidity, but it is difficult to form a unique spatial network structure, which prevents the ultra-high molecular weight polyethylene macromolecular chain from being disentangled, resulting in a decrease in the maleic anhydride grafting rate and the melt flow plasticity, thereby reducing the mechanical properties and wear resistance of the polyamide material.

[0117] It can be seen from the test data of Example 1 and Comparative Example 3 that the mechanical properties and wear resistance of Comparative Example 3 are significantly lower than those of Example 1. The possible reason is that the cross-linking inhibitor zinc dimethyldithiocarbamate is not added during the preparation of the modified ultra-high molecular weight polyethylene, and the cross-linking side reaction of the ultra-high molecular weight polyethylene macromolecular chain will increase, resulting in an increase in the macromolecular cross-linking byproducts of the ultra-high molecular weight polyethylene macromolecular chain, affecting the grafting rate, and then affecting the compatibility of the modified ultra-high molecular weight polyethylene and the polyamide resin, and the mechanical strength is not high.

[0118] From the test data of Example 1 and Comparative Example 4, it can be seen that the tensile strength, bending strength and wear resistance of Comparative Example 4 are all lower than those of Example 1, but the impact strength is slightly higher than that of Example 1. The possible reason is that the mechanical properties, friction coefficient and mass wear of the polyamide material are relatively low due to the lack of addition of poly(m-xylylene adipamide) resin. In addition, since the molecular chain of poly(m-xylylene adipamide) resin contains benzene rings and is a hard and brittle material, the lack of addition will improve the impact properties of the polyamide material.

[0119] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0120] The above is a detailed introduction to the preparation method of a polyamide material provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of ​​the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. Modified ultra-high molecular weight polyethylene, characterized in that: The composition comprises the following components in parts by weight: Ultra high molecular weight polyethylene A 20-40 parts by weight; Ultra high molecular weight polyethylene B 53-61 parts by weight; 6-12 parts by weight of flow modifier; Lubricant A 0.5-1.0 parts by weight; Maleic anhydride 0.9-3 parts by weight; Initiator 0.09-0.3 parts by weight; 0.1-0.2 parts by weight of a cross-linking inhibitor; The viscosity average molecular weight of the ultra-high molecular weight polyethylene A is 1.5-2.5 million; the viscosity average molecular weight of the ultra-high molecular weight polyethylene B is ≥4 million.

2. The modified ultra-high molecular weight polyethylene according to claim 1, characterized in that: The flow modifier is a mixture of hollow glass microspheres and nano-montmorillonite; the addition ratio of the hollow glass microspheres to the nano-montmorillonite in the mixture is 2:

1.

3. The modified ultra-high molecular weight polyethylene according to claim 2, characterized in that: The density of the hollow glass microspheres is 0.95-1.50 g / cm 3 , D90 particle size is 10-30μm, and compressive strength is ≥80MPa.

4. The modified ultra-high molecular weight polyethylene according to claim 1, characterized in that: The lubricant A is silicone powder.

5. The modified ultra-high molecular weight polyethylene according to claim 1, characterized in that: The initiator is one of diisopropylbenzene peroxide (DCP), benzoyl peroxide (BPO) and di-tert-butyl diisopropylbenzene peroxide (BIPB).

6. The modified ultra-high molecular weight polyethylene according to claim 1, characterized in that: The cross-linking inhibitor is zinc dimethyldithiocarbamate.

7. The method for preparing the modified ultra-high molecular weight polyethylene according to any one of claims 1 to 6, characterized in that: The steps include: S1. Ultra-high molecular weight polyethylene A, ultra-high molecular weight polyethylene B, flow modifier, lubricant A, maleic anhydride, initiator and crosslinking inhibitor are placed in a high-speed mixer and mixed uniformly according to weight to obtain a mixture, wherein the mixing time is 3-5 minutes, and the mixing process does not require heating; S2. The mixture is placed in a parallel co-rotating twin-screw extruder for melt grafting and blending, and extrusion granulation is performed. The modified ultra-high molecular weight polyethylene is obtained after cooling, dehydration and air drying; wherein the processing temperature control range of each zone of the parallel co-rotating twin-screw extruder is 170-200°C, the head temperature control range of the parallel co-rotating twin-screw extruder is 190±5°C, and the vacuum degree of the parallel co-rotating twin-screw extruder is ≤-0.08MPa.

8. A polyamide material, characterized in that: The composition comprises the following components in parts by weight: Modified ultra-high molecular weight polyethylene: 10-15 parts by weight, Polyamide resin: 73-89 parts by weight, Poly(m-xylylene adipamide) resin: 4-8 parts by weight, Lubricant B: 0.2-0.5 parts by weight, Auxiliary agent: 1-3 parts by weight; Wherein, the modified ultra-high molecular weight polyethylene is the modified ultra-high molecular weight polyethylene described in any one of claims 1 to 6.

9. The polyamide material according to claim 8, characterized in that: The relative viscosity of the poly(meta-xylylene adipamide) resin is ≥2.0 dl / g.

10. A method for preparing a polyamide material as claimed in claim 8 or 9, characterized in that: The steps include: The modified ultra-high molecular weight polyethylene, polyamide resin, poly(m-xylylene adipamide) resin, lubricant B and auxiliary agents are uniformly mixed according to weight proportions, melt-blended, extruded and granulated through a parallel co-rotating twin-screw extruder to obtain the polyamide material.

Citation Information

Patent Citations

  • Ultrahigh-molecular weight polyethylene modified nylon 66 and preparation method thereof

    CN103436012A